2019
DOI: 10.3847/1538-4357/ab46b6
|View full text |Cite
|
Sign up to set email alerts
|

Double-detonation Models for Type Ia Supernovae: Trigger of Detonation in Companion White Dwarfs and Signatures of Companions’ Stripped-off Materials

Abstract: We have studied double-detonation explosions in double-degenerate (DD) systems with different companion white dwarfs (WD) for modeling type Ia supernovae (SNe Ia) by means of high-resolution smoothed particle hydrodynamics (SPH) simulations. We have found that only the primary WDs explode in some of the DD systems, while the explosions of the primary WDs induce the explosions of the companion WDs in the other DD systems. The former case is so-called Dynamically-Driven Double-Degenerate Double-Detonation (D 6 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 96 publications
1
32
0
Order By: Relevance
“…A detonation could be generated before the WDs are merged to form a single compact star (Moll et al 2014), and this detonation is initiated at the outer envelop that contains a thin and modest amount of helium (Townsley et al 2019). The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…A detonation could be generated before the WDs are merged to form a single compact star (Moll et al 2014), and this detonation is initiated at the outer envelop that contains a thin and modest amount of helium (Townsley et al 2019). The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…In our results, due to the reflection symmetry, the cone shape is always paired on both sides. We expect that, if we allow a single bubble without assuming reflection symmetry, a one-sided feature can emerge, as in more general simulations such as Tanikawa et al (2019) and Gronow et al (2020).…”
Section: Remnant Morphologymentioning
confidence: 97%
“…Such a scenario is viable when the surface energy production is faster than its heat loss by convection or expansion (Jacobs et al 2016). The initial nuclear runaway can be triggered by accretion from its companion star in the single-degenerate scenario or through a violent merger in the double-degenerate scenario (see, e.g., Tanikawa et al 2015Tanikawa et al , 2019. Pure CO matter has a high ignition threshold for its high temperature (∼1-2×10 9 K; e.g., Sato et al 2015), which is shown to be difficult to trigger and sensitive to the way of contact (Dan et al 2012).…”
Section: A2 Sub-chandrasekhar-mass Wd Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will investigate whether these materials can be observed by radiative transfer calculations in near future. We have also investigated whether the explosions of the heavier WDs induce the explosions of the lighter WDs by numerical simulations with various mass combinations of WDs [31]. In all the cases, we have used a CO WD with 1.0M ⊙ for the heavier WDs.…”
Section: Pos(golden2019)046mentioning
confidence: 99%